Analysis of The Effect of Accounting Education, Motivation And Availability of Job Information on Accounting Students' Interest In A Career As An Accountant - Yolanda, Nabila; Izzati, Dina; Zahrani, Vista; Parsi, Citra; Miranda, Aqilah; Arnita, Vina (Indonesian Journal Publisher, 2025)
This study aims to analyze the effect of accounting education, motivation, and the availability of job information on accounting students' interest in a career as an accountant. The phenomenon of shifting student interest in choosing a career outside accounting may threaten the availability of professional accountants in the future. Using a quantitative approach and a systematic survey design, data were collected from 100 students of accounting study programs in Medan who had taken the